Yield and agronomic characteristics of purple corn (Zea mays L.) hybrids with different inbreeding using the AMMI model - Rodríguez-Pérez, Gilberto (2023)
The production of corn (Zea mays L.) in Mexico is deficient despite producing 27 million tons, in the last four years the production of corn in Sonora has increased, producing from 544 to 680 thousand tons in 2018 and 2021 respectively, 97% of the production corresponds to white corn, 3% to yellow corn; however, in colored maize there are no planting records. The objective of this research was to estimate grain yield and its agronomic components in improved purple maize hybrids in southern Sonora. A randomized complete block experimental design was used with three repetitions with the AMMI model, the plots were two rows four meters long with a population density of 100,000 plants per hectare, the variables were: grain yield, seed weight, thousand grains, ear length, grains per row, rows per ear and test weight. The results showed statistical significance between hybrids, years and their interaction in all the variables. The AMMI model was useful to understand the existing genotype-environment interaction between hybrids of mode color in grain yield. The AMMI allowed hybrids 10, 1, 17, 4 and 2 to be identified as more stable in RG, GH, HM and LM for the year 2020. On the other hand, hybrids 9, 12, 3 and 13 in 2019; however, those with the greatest interaction were 7, 16 and 4 presented performances below the general average; hybrids 16, 10, 14 and 19 obtained higher yield, as well as higher PMG, PH GH, and LM. There was a correlation between grain yield with PMG, PH, LM, GH and HM; in PMG there was more association with PH, GH and HM.